2012
DOI: 10.2528/pierb12052506
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Dynamics of a System of Bilaterally Coupled Chaotic Gunn Oscillators

Abstract: Abstract-The dynamics of a system of two bilaterally coupled chaotically oscillating X-band Gunn oscillators (GOs) has been studied by numerical simulation and by hardware experiment. The effect of variation of the coupling strengths between two oscillators in two paths has been explored. The chaotic oscillations in two GOs have become synchronized in most of the cases when coupling factors (CFs) are around 20% or more. However, the transformation of chaotic states of the GOs to quasi-periodic ones has been ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Recently, authors have reported some works on the dynamics of Xband microwave GOs [12][13][14]. In [12] generation of chaotic microwave oscillations in a driven under-biased GO was illustrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, authors have reported some works on the dynamics of Xband microwave GOs [12][13][14]. In [12] generation of chaotic microwave oscillations in a driven under-biased GO was illustrated.…”
Section: Introductionmentioning
confidence: 99%
“…In [12] generation of chaotic microwave oscillations in a driven under-biased GO was illustrated. The bilateral coupling between two such microwave chaotic GOs was thoroughly studied in [13]. In [14] the behavior of a system of BCPGO was studied experimentally and numerically.…”
Section: Introductionmentioning
confidence: 99%